Циклы активности звезды солнечного типа HD 111395 - Дмитриенко, Е. С.; Саванов, И. С.
The results of analysis of the activity of a bright solar-type star HD 111395 are presented in order to compare its photospheric, chromospheric, and coronal activity. The star HD 111395 has been found to be more active than the Sun. The values of the stars's rotation period Prot are in the range from 15.25 to 18.88 days indicating the differential nature of the rotation of stellar surface. Based on data from sectors 23 and 49 from the TESS mission archive the values of the star's spotting parameter and the areas of spots on the surface of HD 111395 (7500 MSH and 8900 MSH for sectors 23 and 49, respectively) were estimated, which exceed the average solar characteristics, but are comparable to the maximum solar level. Pcycl values of 930 days (2.5 years), 1830 days (5.0 years) and 3800 days (10.4 years) were found on the base of the Kamogata Wide-field Survey (KWS) archive and 1800 days (4.9 years) - according to ASAS measurements. Obtained results are compared with data on activity cycles determined by chromospheric manifestations and observed long-term changes in the X-ray flux.
Keywords: Астрофизика